Tax policy at the outskirts of EU: Greenland - Carsten Vesterø Jensen; Søren Bo Nielsen (Copenhagen Business School (CBS), Department of Economics, 2003)
This paper provides an assessment of Greenland's tax system and contemplates changes that may be undertaken in the future to prepare for greater economic self-reliance and for the country's participation in the wider world economy. At the outskirts of Europe, Greenland is an autonomous part of the Danish kingdom, though currently not a member of EU. However, its cooperation with European countries and its dependency on international trade renders it necessary for the tax system in Greenland to be attuned to developments in the rest of the world. Drawing on a thorough international benchmarking analysis of Greenland's tax system, the paper's special focus will be on the corporate tax system and its interplay with personal taxation, as well on as the system of import duties. In particular, we carry out computations of effective marginal and average corporate tax rates, as well as average effective tax burdens on consumption, labour income and capital income, and compare these to similar measures for EU countries. In addition, we outline how Greenland's economic policy in other areas interferes with tax policy. Especially fishery regulation, management of government-owned companies, and housing policy have major implications for the tax system.
hdl:10398/7595
Keywords: H26; I21; J64; 330; international benchmarking; effective tax rates; Greenland